2018
DOI: 10.1302/2058-5241.3.170028
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of total knee arthroplasty in patients with poliomyelitis

Abstract: Total knee arthroplasty (TKA) in patients affected by poliomyelitis is technically challenging owing to abnormal anatomical features including articular and metaphyseal angular deformities, external rotation of the tibia, excessive valgus alignment, bone loss, narrowness of the femoral and tibial canals, impaired quadriceps strength, flexion contractures, genu recurvatum and ligamentous laxity. Little information is available regarding the results and complications of TKA in this challenging group of patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 9 publications
1
25
0
3
Order By: Relevance
“…59,60 The rotational aspect of the hinge is necessary except in very rare neurological cases where the movement must be restricted to flexion–extension. 61…”
Section: Are Hinged Implants Still An Attractive Option In Tka Revision?mentioning
confidence: 99%
“…59,60 The rotational aspect of the hinge is necessary except in very rare neurological cases where the movement must be restricted to flexion–extension. 61…”
Section: Are Hinged Implants Still An Attractive Option In Tka Revision?mentioning
confidence: 99%
“…Esto podría deberse al reto técnico que supone una ATR en pacientes con secuelas de poliomielitis en los que generalmente se presentan, como se mencionó anteriormente, deformidades articulares y metafisarias, aumentada rotación tibial externa, valgos excesivo, pobre calidad del hueso, genu-recurvatum y laxitud ligamentosa, características que pueden alterar los procesos intrínsecos de la cirugía, como la realización de los canales para los vástagos tibial y femoral (1-2). También así la colocación adecuada de dichos vástagos y el fraguado del cemento, que al tratarse habitualmente de huesos osteopénicos, puede generar con facilidad alteraciones no deseadas en la alineación del el elemento protésico (8).…”
Section: Discussionunclassified
“…La fuerza muscular del cuádriceps parece ser un factor pronóstico importante para los resultados funcionales y cuando esta es menor que la antigravitatoria, el uso de implantes constreñidos está recomendado (8). Además, el uso de implantes abisagrados está indicado en pacientes más severamente afectados con pobre fuerza muscular que no proporciona estabilidad intrínseca, aumentando el riesgo de recurrencia de hiperextensión de rodilla y laxitud ligamentosa (9).…”
Section: Introductionunclassified
“…Tigani et al [4] had justified that modern day implants with RHK designs mimics normal kinematics of knee with reduced stress on implant bone interface. In one study [5] , it suggested that if quadriceps power in less than antigravity strength (<3/5), Results with hinged design are better than conventional design.…”
Section: Discussionmentioning
confidence: 99%